Traffic Light Control System / Firdaus Abdullah and Sri Ayu Mohd. Saad - Abdullah, Firdaus; Mohd. Saad, Sri Ayu (2001)
Traffic Light Control System is a simple circuit that produces a signal of traffic light . It is important when we’re using a road . This circuit is design to give an easy work to people when they drive vehicles on the road and also to pedestrian if they want to cross the road The main part of this circuit is - EPROM 2716 , variables resistor, IC 555 , IC 74LS93 , IC 74LS123 , relay, voltage supply ( power supply). In future , we are not using this circuit anymore to design a traffic light because now they already modified the circuit - not using the lamp but change it to light emitting diode ( LED ). It will reduce the maintenances . However , this circuit can also be applied for other application like for construction work , lift and etc .